Basic Financial Management Training for MSMEs to Enhance Efficiency and Business Sustainability: Pelatihan Manajemen Keuangan Dasar bagi UMKM untuk Meningkatkan Efisiensi dan Keberlanjutan Bisnis - Karnasi, Reniati; Lestari, Henny Setyo; Faisal, Aekram; Ramadhanti, Mutiara; Anggraeni, Dewi (Yayasan Ahmar Cendekia Indonesia, 2025)
This article addresses the issue of weak financial management among micro, small, and medium enterprises (MSMEs), which has an impact on business efficiency and sustainability. The focus of this community service program was basic financial management training for members of the Komunitas Sukses Berjamaah Indonesia (KSBI) aimed at strengthening bookkeeping, cash flow management, and the separation of personal and business finances. The objective was to improve financial literacy and practical skills, thereby fostering disciplined financial behavior and broader access to financing. The method employed a participatory approach, combining lectures, case studies, bookkeeping simulations, group discussions, and questionnaire-based evaluations, supported by field observation and follow-up. The training was conducted in South Jakarta with 20 participants from the trade, culinary, and service sectors. Results showed that 85% of participants considered the material relevant, 80% assessed the delivery as clear, 75% successfully prepared a simple cash flow report, and 78% committed to separating personal and business finances. The program also fostered solidarity, peer learning habits, and the emergence of local leaders, thereby enhancing financial efficiency while supporting the long-term sustainability of KSBI members’ businesses. These findings are consistent with the literature on financial literacy and community empowerment. Abstrak Artikel ini mengangkat isu rendahnya manajemen keuangan pada UMKM yang berdampak pada efisiensi operasional dan keberlanjutan bisnis. Fokus pengabdian adalah pelatihan manajemen keuangan dasar bagi anggota Komunitas Sukses Berjamaah Indonesia (KSBI) untuk memperkuat pencatatan, arus kas, dan pemisahan keuangan pribadi–usaha. Tujuan kegiatan ialah meningkatkan literasi dan keterampilan praktis sehingga terbentuk perilaku keuangan yang tertib serta akses pembiayaan yang lebih luas. Metode menggunakan pendekatan partisipatif melalui penyampaian teori, studi kasus, simulasi pencatatan, diskusi, dan evaluasi kuesioner, disertai observasi lapangan dan tindak lanjut. Pelatihan dilaksanakan satu hari di Jakarta Selatan dengan 20 peserta dari sektor perdagangan, kuliner, dan jasa. Hasil menunjukkan 85% peserta menilai materi relevan, 80% menilai penyampaian jelas, 75% mampu menyusun arus kas sederhana, dan 78% berkomitmen memisahkan keuangan. Teridentifikasi pula munculnya solidaritas, kebiasaan belajar bersama, dan figur pemimpin lokal, yang memperkuat efisiensi pengelolaan sekaligus menopang keberlanjutan usaha anggota KSBI. Temuan ini konsisten dengan literatur tentang literasi keuangan dan pemberdayaan.